Difference between revisions of "009B Sample Midterm 1, Problem 1"
Jump to navigation
Jump to search
Line 11: | Line 11: | ||
|- | |- | ||
| | | | ||
− | ::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -5px">u=\ln(x).</math> Then, <math style="vertical-align: -13px">du=\frac{1}{x}dx.</math> | + | ::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -5px">u=\ln(x).</math> Then, <math style="vertical-align: -13px">du=\frac{1}{x}dx.</math> Thus, |
|- | |- | ||
| | | | ||
− | :: | + | ::<math>\begin{array}{rcl} |
+ | \displaystyle{\int \frac{\ln x}{x}~dx} & = & \displaystyle{\int u~du}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{u^2}{2}+C}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{(\ln x)^2}{2}+C.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
'''Solution:''' | '''Solution:''' | ||
Line 22: | Line 28: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=1+x^3</math> | + | |We need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=1+x^3.</math> Then, <math style="vertical-align: 0px">du=3x^2dx</math> and  <math style="vertical-align: -13px">\frac{du}{3}=x^2dx.</math> |
|- | |- | ||
− | |Therefore, the integral becomes  <math style="vertical-align: -13px">\frac{1}{3}\int \sqrt{u}~du</math> | + | |Therefore, the integral becomes  |
+ | |- | ||
+ | | | ||
+ | ::<math style="vertical-align: -13px">\frac{1}{3}\int \sqrt{u}~du.</math> | ||
|} | |} | ||
Line 32: | Line 41: | ||
|We now have: | |We now have: | ||
|- | |- | ||
− | | | + | | |
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\int x^2\sqrt{1+x^3}~dx} & = & \displaystyle{\int x^2\sqrt{1+x^3}~dx}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{1}{3}\int \sqrt{u}~du}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{2}{9}u^{\frac{3}{2}}+C}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{2}{9}(1+x^3)^{\frac{3}{2}}+C.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 39: | Line 57: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |Again, we need to use <math>u</math>-substitution. Let <math style="vertical-align: -5px">u=\sin(x)</math> | + | |Again, we need to use <math>u</math>-substitution. Let <math style="vertical-align: -5px">u=\sin(x).</math> Then, <math style="vertical-align: -5px">du=\cos(x)dx.</math> Also, we need to change the bounds of integration. |
|- | |- | ||
− | |Plugging in our values into the equation <math style="vertical-align: -5px">u=\sin(x)</math> | + | |Plugging in our values into the equation <math style="vertical-align: -5px">u=\sin(x),</math> we get <math style="vertical-align: -15px">u_1=\sin\bigg(\frac{\pi}{4}\bigg)=\frac{\sqrt{2}}{2}</math> and <math style="vertical-align: -16px">u_2=\sin\bigg(\frac{\pi}{2}\bigg)=1.</math> |
|- | |- | ||
− | |Therefore, the integral becomes | + | |Therefore, the integral becomes |
|- | |- | ||
| | | | ||
+ | ::<math style="vertical-align: -19px">\int_{\frac{\sqrt{2}}{2}}^1 \frac{1}{u^2}~du.</math> | ||
|} | |} | ||
Line 52: | Line 71: | ||
|- | |- | ||
|We now have: | |We now have: | ||
− | |||
− | |||
− | |||
− | |||
|- | |- | ||
| | | | ||
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\int _{\frac{\pi}{4}}^{\frac{\pi}{2}} \frac{\cos(x)}{\sin^2(x)}~dx} & = & \displaystyle{\int_{\frac{\sqrt{2}}{2}}^1 \frac{1}{u^2}~du}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\left.\frac{-1}{u}\right|_{\frac{\sqrt{2}}{2}}^1}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{-\frac{1}{1}-\frac{-1}{\frac{\sqrt{2}}{2}}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{-1+\sqrt{2}.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
Revision as of 12:50, 18 April 2016
Evaluate the indefinite and definite integrals.
- a)
- b)
Foundations: |
---|
How would you integrate |
|
|
Solution:
(a)
Step 1: |
---|
We need to use -substitution. Let Then, and |
Therefore, the integral becomes |
|
Step 2: |
---|
We now have: |
|
(b)
Step 1: |
---|
Again, we need to use -substitution. Let Then, Also, we need to change the bounds of integration. |
Plugging in our values into the equation we get and |
Therefore, the integral becomes |
|
Step 2: |
---|
We now have: |
|
Final Answer: |
---|
(a) |
(b) |